Recycled Aggregate Self-curing High-strength Concrete - Alaa Ali Bashandy; Noha M. Soliman; Mahmoud Hamdy Abd Elrahman (Salehan Institute of Higher Education, 2017)
The use of recycled aggregates from demolished constructions as coarse aggregates for concrete becomes a need to reduce the negative effects on the environment. Internal curing is a technique that can be used to provide additional moisture in concrete for more effective hydration of cement to reduce the water evaporation from concrete, increase the water retention capacity of concrete compared to the conventionally cured concrete. High strength concrete as a special concrete type has a high strength with extra properties compared to conventional concrete. In this research, the combination of previous three concrete types to obtain self-curing high-strength concrete cast using coarse recycled aggregates is studied. The effect of varying water reducer admixture and curing agent dosages on both the fresh and hardened concrete properties is studied. The fresh properties are discussed in terms of slump values. The hardened concrete properties are discussed in terms of compressive, splitting tensile, flexure and bond strengths. The obtained results show that, the using of water reducer admixture enhances the main fresh and hardened properties of self-curing high-strength concrete cast using recycled aggregate. Also, using the suggested chemical curing agent increased the strength compared to conventional concrete without curing.